2018
DOI: 10.1080/16549716.2018.1527556
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening health technology assessment systems in the global south: a comparative analysis of the HTA journeys of China, India and South Africa

Abstract: Background: Resource allocation in health is universally challenging, but especially so in resource-constrained contexts in the Global South. Pursuing a strategy of evidence-based decision-making and using tools such as Health Technology Assessment (HTA), can help address issues relating to both affordability and equity when allocating resources. Three BRICS and Global South countries, China, India and South Africa have committed to strengthening HTA capacity and developing their domestic HTA systems, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 45 publications
2
56
0
1
Order By: Relevance
“…Although HTA remains relatively under-developed in SSA, there is growing political commitment and policy interest 14,15 . Priority setting is inevitable: the question is not whether, but rather how, to set them.…”
Section: Discussionmentioning
confidence: 99%
“…Although HTA remains relatively under-developed in SSA, there is growing political commitment and policy interest 14,15 . Priority setting is inevitable: the question is not whether, but rather how, to set them.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are many challenges resulting from the technology itself, end-users and environments that continue to undermine efforts to provide UHC in this regard. Research in three BRICS and Global South countries, China, India and South Africa, showed similar barriers to strengthening and developing health technology assessment systems such as lack of expertise, weak health data infrastructure, rising healthcare costs, fragmentation of healthcare systems and growth in noncommunicable diseases [60].…”
Section: Medical Products Vaccines and Technologiesmentioning
confidence: 96%
“…For example, in the overwhelming majority of countries in SSA, value sets are simply not available for the most commonly, and widely understood, generic HRQoL tool, the EQ-5D (five dimensions). The adoption of QALYs is feasible in SSA [65], and awareness raising together with action and support for research efforts at developing value sets for Ghana through peer or South-South channels may be an important means of methods development [7]. This highlights the importance of having a reference case [22] that signals preference (and creates a demand) for certain types of data [78].…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…Health technology assessment (HTA) represents a commonly used approach to synthesising evidence on the effectiveness and costs of an intervention, which also aims to consider social value judgements as part of a process to inform efficient and equitable resource allocation [1,2]. While the specific methods and processes vary according to context, HTA informs health spending decisions in almost all high-income countries [3], and increasingly in middle-income countries such as Thailand [4,5] and South Africa [6,7], and regions including the Middle East and North Africa [8,9]. The World Health Assembly Resolution of 2014 on Health Intervention and Technology Assessment recognizes the importance of this approach as a key element of any strategy for achieving universal health coverage (UHC) [2,10].…”
Section: Introductionmentioning
confidence: 99%